ANALISIS PENGARUH PENGGUNAAN WIFI ZONE TERHADAP PROSES BELAJAR MENGAJAR PADA PROGRAM STUDI MULTIMEDIA - ., Fatayat (SEMIRATA 2015, 2015)
Today competition in higher education appears increasingly stringent. Rapid global changes in terms of technological advances (products, services or processes) as well as the social and economic life of society, should encourage the holding of a precaution through policy and strategy of college so that later can still survive in all fields. This study aims to determine the effect of a positive and significant changes in any obtained against the student learning process and the positive and negative impacts on the efficiency ime learn than when using a manual system and to find out the variables which have an influence on the infrastructure domain. The research conducted is in the form of an explanatory research which means research that explains the whole of the object under study in certain limits. Data collection method used is survey method used simple random sampling technique (simple random sample) with a target Respondents are end users (end-users) in all types of organizations either (Government, Education, Perusahaah and social), which is commonly used as an information system AIDS. The population in this study were all students and faculty in particular the Multimedia Studies Program in their full amount to 130 people and a sample of this research for a number of students taken a number of 87 students. The samples in this study is called stratified random sampling, which means that if a diguankan study population showed a good startifikasi strata of large, medium small maupu against the population. In general, the purpose of this study was to analyze the effect of infrastructure especially in the way the Wifi Zone's global communication challenges of globalization are expected to be online that can be applied. Data collection method used is survey method using simple random sampling (simple random sample) with a target respondents are end users (end-users) in all types of organizations (government, education, enterprise and social) that regular use of information systems as a tool Bantu. In this study the technique of determining the sample taking of the semester I and III and the teaching staff penelitaian The results showed that the average value of the overall score obtained for the independent variables representing the level of satisfaction waifi use and effect singnifikan with Kuwat enough correlation to the efficiency of the use of technology wifi on the teaching and learning process is the stability / reliability, accuracy, timeliness of documentationÂ and support system. Â  Keyword: Wifi, Simple Random Sampling Technique, singnifikan. Â